A New Mining Scheme for Hanging-Wall Ore-Body during the Transition from Open Pit to Underground Mining: A Numerical Study. (17th October 2018) - Tan, Baohui; Ren, Fengyu; Ning, Youjun; He, Rongxing; Zhu, Qiang
Abstract : A new mining scheme by employing the induced caving mining method to exploit hanging-wall ore-body during the transition from open pit to underground mining is proposed. The basic idea is to use the mined-out area generated by the planned mining of the hanging-wall ore-body to absorb the collapsed slope body, so as to avoid the influence of the inner-slope mining to the normal open-pit mining and guarantee mining efficiency during the transition stage. Numerical simulation study on the process of induced caving mining of hanging-wall ore-body is carried out based on the practical engineering setting of the Hainan iron mine, China, by employing the numerical method of discontinuous deformation analysis (DDA). The impact of rock mass structure on the mechanism of slope instability development and the mining hazard assessment in the new mining scheme is investigated. The influence of mining sequence on slope instability development and mining safety is also analyzed by taking the hanging-wall ore-body mining under the southern anti-dip slope at the Hainan iron mine as an example, and eventually a reliable mining scheme via induced caving is obtained. The numerical study proves the feasibility of the proposed new mining scheme for hanging-wall ore-body and provides theoretical and technical support for its application in practical mining activities.